2018
DOI: 10.1002/2017jb015247
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Appraisal of the “Day” Diagram

Abstract: The “Day” diagram (Day et al., 1977, https://doi.org/10.1016/0031-9201(77)90108-X) is used widely to make inferences about the domain state of magnetic mineral assemblages. Based on theoretical and empirical arguments, the Day diagram is demarcated into stable “single domain” (SD), “pseudo single domain” (“PSD”), and “multidomain” (MD) zones. It is straightforward to make the necessary measurements for a sample and to plot results within the “domain state” framework based on the boundaries defined by Day et al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
137
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(148 citation statements)
references
References 158 publications
(414 reference statements)
9
137
0
2
Order By: Relevance
“…Figure shows the magnetic hysteresis loops of Samples P‐72/4 and ST‐1 at the initial state and at the end of the thermal treatment. Whereas these loops are consistent with the presence of a mixture of multidomain and pseudo single‐domain (PSD) particles at the initial state of the thermal treatment, they are characteristic of single‐domain (SD) and small PSD particles at the end of the thermal treatment (e.g., Roberts et al, ).…”
Section: Rock Magnetic Resultsmentioning
confidence: 75%
“…Figure shows the magnetic hysteresis loops of Samples P‐72/4 and ST‐1 at the initial state and at the end of the thermal treatment. Whereas these loops are consistent with the presence of a mixture of multidomain and pseudo single‐domain (PSD) particles at the initial state of the thermal treatment, they are characteristic of single‐domain (SD) and small PSD particles at the end of the thermal treatment (e.g., Roberts et al, ).…”
Section: Rock Magnetic Resultsmentioning
confidence: 75%
“…(i) Day and (j) Néel diagrams for submarine basaltic glass (SBG) and extrusive rocks from the Azores Islands (Portugal), Mt St Helens (USA), Vesuvius (Italy), and Lascar (Chile). Hysteresis results for the various data sets have been discussed previously by Roberts et al (), Roberts, Tauxe, et al, ) with citation of source references. The region for USD + SP magnetite (Figure b) from Tauxe et al () is indicated on the respective Néel diagrams.…”
Section: Resultsmentioning
confidence: 84%
“…We, therefore, do not recommend routine use of the Day, Néel, Borradaile, and Fabian diagrams (Borradaile & Lagroix, ; Day et al, ; Fabian, ; Néel, ) unless they are used for pure magnetic mineral components. Reasons for this recommendation are provided by Roberts, Tauxe, et al (), where the focus is on the Day diagram, but most of the same issues also apply to the Néel and Borradaile diagrams. The Lascu diagram (Lascu et al, ) is also based on bulk parameters, but it is designed for use with extensive additional mineral magnetic information to constrain interpretation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations